Decision Support System to Select Elective Courses Using Hybrid AHP-Promethee Method - Haryono Setiadi; Noor Azizah Mosaik Suni; Dewi Wisnu Wardani (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2022)
The selection of elective courses is often confusing for students as indicated by the initial survey of class 2015 -2018 students in the Informatics Department of Sebelas Maret University which showed that 88,9% needed a system to assist in selecting elective courses. This study was conducted to accommodate students’ requirements by designing the decision support system to recommend elective courses by combining AHP and PROMETHEE methods. AHP was used to weight the criteria, after which they were then ranked using the PROMETHEE such that the elective courses were sorted partially using PROMETHEE I as scenario 1 and completely through PROMETHEE II as scenario 2. The accuracy test showed that scenarios 1 and 2 were 67.4% and 60.4%, respectively, accurate.